A Novel Type of Signalling from DNA Damage Under ATP Stress in Huntington’s Disease - Bowie, Laura (My University, 2018)
Huntington’s disease is an autosomal dominantly inherited neurodegenerative disorder characterized by degeneration of striatal and cortical neurons. The neurons in these regions are particularly energy-demanding and need to maintain high levels of oxidative phosphorylation to support cellular activities. Reactive oxygen species are generated as a byproduct of oxidative phosphorylation and can damage DNA and other biomolecules if not properly metabolized. In HD, there is elevated oxidative DNA damage and impaired DNA damage repair, likely due to impaired function of the mutant huntingtin protein in base excision repair (BER). Previous studies have shown that mutant huntingtin is hypo-phosphorylated at serines 13 and 16 in the N17 domain, and that restoring phosphorylation can reestablish normal protein function and is protective in HD. In this thesis, we show that a metabolite of the DNA damage product N6- furfuryladenine (N6FFA), kinetin triphoshate (KTP) increases N17 phosphorylation through casein kinase 2 (CK2) by acting as an ATP analog, with protective effects in cell and animal models of disease. We additionally show N6FFA increases the activity of CK2 on other substrates, specifically p53. We hypothesize that in times of ATP stress CK2 can utilize KTP as an alternate energy source, promoting DNA repair and cell viability. In HD, inefficient BER inhibits generation of KTP and promotes hypo- phosphorylation of CK2 substrates, which can be overcome by exogenous addition of N6FFA. Additionally, we show that another DNA-responsive kinase, PKCζ, can also phosphorylated N17, potentially priming this domain for CK2 phosphorylation. Finally, we propose that the protective effects of N6FFA may be via a two-pronged pathway, involving both CK2 and the mitochondrial quality control kinase, PINK1. Thus, this thesis presents a novel mechanism where a product of DNA damage acts as a phosphate source for critical kinases in DNA repair and mitochondrial maintenance in conditions where ATP levels are low.
Keywords: Huntington's disease; DNA damage; Bioenergetics; DNA damage repair